1979
DOI: 10.1111/j.1748-1716.1979.tb06444.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of blood flow in the dog kidney: I. Saturation rates for inert diffusible tracers, 125I‐iodoantipyrine and tritiated water, versus uptake of microspheres under control conditions

Abstract: Disparate reports on intrarenal blood flow distribution prompted a direct comparison between microspheres (Ms) and inert diffusible tracers (DT). The "tissue sampling technique" for estimating local flow with DT (Kety) was adapted for the dog kidney, using 125I-iodoantipyrine (1-Ap) and tritiated water (THO). Ms (15 micron) were injected 2-3 min prior to 10-15 s DT infusion made during continuous 1 s arterial blood sampling. Tracers were measured in 7 to 20 samples from each of the following zones: Outer, midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…35], The i3,Xe an d 85Kr techniques are also open to criticism [16. 17], It might be added that during marked changes in renal vascular resistance an al tered intrarenal blood flow profile is ob tained with microspheres, whereas simulta neous l25I-iodoantipyrine measurements in dicate no such change [36], This illustrates that the discrepant results obtained with microspheres and diffusible indicators are by no means restricted to HH. Thus, the generally accepted concept of a relatively better maintained blood flow in inner renal zones during HH [6] should be reconsi dered.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…35], The i3,Xe an d 85Kr techniques are also open to criticism [16. 17], It might be added that during marked changes in renal vascular resistance an al tered intrarenal blood flow profile is ob tained with microspheres, whereas simulta neous l25I-iodoantipyrine measurements in dicate no such change [36], This illustrates that the discrepant results obtained with microspheres and diffusible indicators are by no means restricted to HH. Thus, the generally accepted concept of a relatively better maintained blood flow in inner renal zones during HH [6] should be reconsi dered.…”
Section: Discussionmentioning
confidence: 77%
“…Because of the few studies in the rat and of discrepant results, which may relate to methodological inadequacies [16][17][18] and/or to species differences, we decided to measure total and local renal blood flow using the H, gas and l25I-iodoantipyrine techniques. Both methods are based on the principle of pro portionality between local blood flow and rate of indicator washout/uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Shunting of heat between arterial and venous vessels has been reported and is thought to be responsible for slow clearance of this extremely "diffusible" indicator from the superficial cortex (23,24). Similarly, it has been suggested that diffusion of ['251]iodoantipyrine between deeper cortical vessels may be responsible for the observation that blood flow estimated in the more superficial regions is less than that obtained with microspheres (30). The observation that Pco2 is not elevated in tubular fluid of the medulla is also consistent with countercurrent diffusion in the cortex (31).…”
Section: Resultsmentioning
confidence: 98%
“…In the other half, it was placed in the acid solution to produce "4CO2. The acid solution contained 12 mM HCl in 0.1 g/dl bovine serum albumin-saline solution and the alkaline solution contained 30 mM of the buffer Hepes in Ringer's lactate at pH 8.4. Hepes buffer was used rather than a CO2-HCO-system to ensure that a constant pH was rapidly attained.…”
Section: General Proceduresmentioning
confidence: 99%
“…Radiolabelled plastic micro spheres with diameters of 10-15 pm satisfy closely the second requirement, and have been widely used since their introduction by McNay and Abe [1970]. However, many studies indicate that the microspheres are subject to ski rnming at the origin of the affer ent arterioles and therefore underestimate blood flow in deep glomeruli, and overesti mate superficial glomerular flow [Aukland, 1980: Bankir et al, 1979Clausen et al, 1980;Mimran and Casellas, 1979;0J}ord and Clausen, 1983], A promising attempt to avoid this shortcoming was the use of antiglomerular basement membrane antibody, which is dissolved in plasma and is therefore not subject to skimming. However, while the first report by Wallin et al [1971] showed 96% glomerular extraction of the antibody in one passage through the dog kidney, later studies in dogs [Stein et al, 1973] and rats [Trin Trang Tan et al, 1978] gave far from complete extraction -about 40%.…”
Section: Introductionmentioning
confidence: 99%